Evolution of the bearing failure map of pinned flax composite laminates aged in marine environment. (15th April 2020) - Fiore, V.; Calabrese, L.; Scalici, T.; Valenza, A.
Abstract: Aim of the present paper is to evaluate how the bearing behavior of pinned flax composites can be influenced by their exposition to critical environment such as marine one. To this scope, flax fibers/epoxy pinned laminate was exposed up to 60 days to salt-fog environment, according to ASTM B 117 standard. In particular, samples having different hole diameter (D), laminate width (W), and hole center to laminate free edge distance (E) have been tested under single lap bearing tests at varying the aging exposition time. Following this procedure, an experimental 2D failure map clustering main failure modes was created by placing the experimental results in the plane E/D versus W/D ratios, and its variation was analyzed at varying the aging exposition. Experimental results showed that environmental aging induced modification on the mechanical performances of the pinned composite. Furthermore, the failure map, defined by E/D and W/D ratios axes, evidenced a progressive modification of damage mechanisms transitions, at increasing the exposition time. In particular, due to significant reductions of tensile and shear strengths of flax laminate, the progressive fracture by bearing mode was not observed for aged samples, replaced by premature and catastrophic shear out and net tension mechanisms. Graphical abstract: Image 1 Highlights: Bearing behavior of pin-loaded flax laminates was investigated in severe environmental conditions. Bearing stress evolution and failure mechanisms were evaluated at varying pin diameter and hole to sample edge distance. Salt-fog aging induced modification on the mechanical performances of the pinned composite joint. Failure map was developed showing a progressive modification of damage mechanisms transitions at increasing aging time. Threshold values of E/D and W/D at varying salt-fog exposition time were defined.